Multi-phasic life-threatening anaphylaxis refractory to epinephrine managed by extracorporeal membrane oxygenation (ECMO): A case report - Grafeneder, Juergen; Ettl, Florian; Warenits, Alexandra-Maria; Buchtele, Nina; Lobmeyr, Elisabeth; Staudinger, Thomas; Schwameis, Michael; Sperr, Wolfgang R.; Gelbenegger, Georg; Schoergenhofer, Christian; Jilma, Bernd (Frontiers in Allergy, 2022)
We present the case of a 52-year-old patient suffering from multi-phasic life-threatening anaphylaxis refractory to epinephrine treatment. ECMO therapy was initiated as the ultima ratio to stabilize the patient hemodynamically and during severe bronchospasms. ECMO treatment was successfully weaned after 4 days. Mastocytosis was diagnosed as the underlying condition. Although epinephrine is recommended as first-line treatment for anaphylaxis, this impressive case provides clear evidence of its limited therapeutic success and emphasizes the need for causal therapies.